Pesticide exposures in a malarious and predominantly farming area in Central Ghana - Ae-Ngibise, Kenneth Ayuurebobi (Afr J Environ Sci Tech, 2015)
In areas where malaria is endemic, pesticides are widely deployed for vector control, which has contributed to reductions in malaria deaths. Pesticide use for agrarian purposes reduces pest populations, thus improving crop production and post-harvest losses. However, adverse health effects have been associated with pesticide exposure, ranging from skin irritation to neurotoxicity and carcinogenicity. Though misuse of these pesticides can lead to widespread potential dangers, the debilitating effects are usually underappreciated in many developing countries. To evaluate the pattern of pesticide usage among rural communities in the Kintampo area of Ghana, a cross-sectional survey was conducted among 1455 heads of households randomly sampled from among 29,073 households in the Kintampo Health and Demographic Surveillance System area of Ghana to estimate the prevalence of pesticide use and indications for use among this rural populace. Seventy-one percent (1040/1455) of household heads reported having used pesticides on either their farms or homes, most commonly for control of weeds (96.4%, 1003/1040) or insects (85.4%, 888/1040). Dichlorodiphenyltrichloroethane (DDT) was used by 22.9% (238/1040) of respondents. The majority of households who reported use of pesticides said women in their households assisted in the spraying efforts (69.3%, 721/1040); of these women, 50.8% (366/721) did so while carrying their babies on their backs. Only 28.9% (301/1040) of the study participants wore protective devices during pesticide applications. Frequent symptoms that were reported after spraying, included cough (32.3%; 336/1040), difficulty in breathing (26.7%; 278/1040) and skin irritation (39.0%; 406/1040). Pesticide use among community members in the Kintampo area of Ghana is common and its potential health impacts warrant further investigation.